Analysis of the Responses of Science Teacher Candidates to Force Concept Inventory by Concentration Factor - Ezberci̇ Çevi̇k, Ebru; Kurnaz, Mehmet Altan (Horizon Research Publishing Co., Ltd., 2019)
This study aims to obtain information about the modelling situations related to the topic by performing concentration analysis of teacher candidates' responses to Force Concept Inventory (FCI). The research was conducted using survey model, which is a quantitative research method. The study was carried out in the fall semester of the academic year 2015–2016 among 95 freshman teacher candidates enrolled in the Science Education Program of the Faculty of Education at a university in the Western Black Sea region. The data collection tool employed was FCI. In this context, concentration score, concentration factor and concentration deviation formulas were used. In light of the results obtained, it was determined that the responses of teacher candidates correspond to the null model, meaning that it is a result of a random reaction. It was suggested that this method of analysis could be used to develop more effective multiple-choice tests and comprehensively assess the learning situation of a class in depth.
Keywords: 4. Education